An experimental research on GPS based boundary intruding boat monitoring system - Puviarasi, R.; Mageshwaran, M.; Ramalingam, Mritha; Boselin Prabhu, S. R. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Boundary detection and alert system is a straightforward and effective idea, which utilizes Internet of Things technology. By utilizing this framework border monitoring is 100% protected and secure. It naturally alarms the intruder when the vehicle goes over the specific range in borders. This is finished by a sensor called Global positioning system (GPS). It detects the current position of the vehicle and switch on the caution framework naturally. In this anticipate, no need of manual operations like on time and off time setting. GPS and IoT are the fundamental segments of the task. The resistances of the alert system changes as per the distance between the current position of the vehicle and the border get decreased or increased.